Bridge Collapse Frequencies versus Failure Probabilities - Proske, Dirk (Risk Engineering,, 2018)
This monograph provides a comparative study between failure probabilities and collapse frequencies in structural bridge engineering. The author presents techniques to resolve and extend the limitations of both parameters, taking also into account the time dependency of both parameters. The book includes available data and case studies and thus presents patterns to identify potential weaknesses and challenges in bridge maintenance. The target audience primarily comprises practicing engineers in the field of bridge engineering, but the book may also be beneficial for academic researchers alike.